DETERMINAN FEE AUDIT - Baldric Siregar; Mutiara Indah Lestari (Fakultas Bisnis UKDW, 2015)
ABSTRACT This study aims to examine the factors that affect audit fees. Factors examined include factors derived from the entity (client) and the factors derived from the auditor. The sample of this research is that companies listed in Indonesia Stock Exchange for the period 2007- 2008. The existence of audit fee disclosure in the financial statements or annual report is the main requirement for a company used as a sample. The hypotheses are tested using multiple regression. Empirical evidence shows that the size and complexity of the entity have positive influences on audit fees. Both of these factors are factors derived from the entity. In addition, the audit reputation has a positive influence on audit fees. This audit reputation is a factor derived from the auditor. Other factors are tested as risk, internal audit, audit committee, financial condition, and audit tenure have no influence on the audit fee. Keywords: audit fee, client size, risk, entitas complexity, auditor reputation, internal audit, audit committee, audit tenure, client financial condition. ABSTRAK Penelitian ini bertujuan untuk menguji faktor-faktor yang mempengaruhi biaya audit. Faktor yang diteliti meliputi faktor yang berasal dari entitas (klien) dan faktor-faktor yang berasal dari auditor. Sampel dari penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesia untuk periode 2007-2008. Adanya pengungkapan biaya audit dalam laporan keuangan atau laporan tahunan adalah syarat utama untuk sebuah perusahaan yang digunakan sebagai sampel. Hipotesis diuji dengan menggunakan regresi berganda. Bukti empiris menunjukkan bahwa ukuran dan kompleksitas entitas memiliki pengaruh positif pada biaya audit. Kedua faktor ini adalah faktor-faktor yang berasal dari entitas. Selain itu, reputasi audit memiliki pengaruh positif pada biaya audit. Reputasi Audit ini merupakan faktor yang berasal dari auditor. Faktor-faktor lain diuji sebagai risiko, audit internal, komite audit, kondisi keuangan, dan masa jabatan audit tidak memiliki pengaruh pada biaya audit. Kata kunci: biaya audit, ukuran klien, risiko, kompleksitas entitas, reputasi auditor, audit internal, komite audit, masa jabatan audit, kondisi keuangan klien